PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA KARYAWAN PADA PT. CILPAN FINANCE TANGERANG II - Roni Fadli; Sri Mulyani; Setianingsih Setianingsih (Gapenas Publisher, 2022)
The purpose of this study is to determine the influence of motivation and discipline on performance in universities. Cilpan Finance Tangerang II. This study used quantitative methods, the population size was 51 respondents with a saturated type of sampling, namely all employees at PT. Bina Putra Makmur Nusantara. Data collection using questionnaires distributed to PT. Cilpan Finance Tangerang II. The collected data were then analyzed using validity test, reability test, classical assumption test, simple linear regression test, multiple linear regression test, coefficient of determination test and hypothesis test with the SPSS Version 25 assistance program. Compensation variables negatively affect the performance of PT. Cilpan Finance Tangerang II, based on the results of the analysis of the influence of factors affecting turnover intention shows a calculation of < ttabel, namely -2,720 < 2,009, sig 0.009 < probability 0.05. Motivation variables have a positive and significant effect on performance at PT. Cilpan Finance Tangerang II, Motivation variables have the most dominant influence on performance by calculating > ttabel which is 4.652 > 2.009, and sig 0.000 < probability 0.005. The motivational and disilin variables together and simultaneously have a pore and significant effect on the performance of pt. Cilpan Finance Tangerang II, because the calculation is greater than the ftabel value of 137.048 > 3.19 with a significant level of < 0.05 which is 0.000